miR-186 Inhibits Liver Cancer Stem Cells Expansion via Targeting PTPN11 - Yao, Haochen; Yang, Ziting; Lou, Yan; Huang, Juanjuan; Yang, Pinghua; Jiang, Weiqi; Chen, Shuai (Frontiers in Oncology, 2021)
MicroRNAs (miRNAs) participated in the regulation of tumorigenesis, progression, metastasis, recurrence and chemo-resistance of cancers. However, the potential function of miRNAs in cancer stem cells (CSCs) or tumor-initiating cells (T-ICs) was not clearly elucidated. In the present study, we found that miR-186 expression was reduced in liver CSCs. Functional studies showed that miR-186 knockdown facilitated liver CSCs self-renewal and tumorigenesis. Conversely, forced miR-186 expression suppressed liver CSCs self-renewal and tumorigenesis. Mechanically, miR-186 downregulated PTPN11 via binding to its 3’-UTR in liver CSCs. The correlation of miR-186 and PTPN11 was confirmed in Hepatocellular carcinoma (HCC) patients’ tissues. Further study showed that interference of PTPN11 can abolished the discrepancy between miR-186 mimic and control HCC cells in self-renewal and the proportion of CSCs. Additionally, we found that miR-186 overexpression HCC cells were more sensitive to cisplatin treatment. Clinical cohort analysis showed that HCC patients with high miR-186 were benefited more from transcatheter arterial chemoembolization (TACE) treatment. In conclusion, our study demonstrates a new regulation mechanism of liver CSCs, a new target for HCC, and a biomarker for postoperative TACE.